Participant Perspectives on Community Qigong for People with Multiple Sclerosis - Lita Buttolph; Lindsey Wooliscroft; Ryan Bradley; Heather Zwickey (Mary Ann Liebert, 2023)
Introduction: Multiple sclerosis (MS) is a progressive neurodegenerative disorder affecting motor and nonmotor function including physical and cognitive decline, fatigue, anxiety, and depression. Qigong is a mind?body self-care practice with the potential to address MS symptoms. Publicly available community qigong classes may provide opportunities for people with MS to access qigong, but little is known about the risks and benefits. A mixed methods study of community qigong was conducted for people with MS. In this article, the results of this qualitative analysis to identify benefits and challenges faced by people with MS attending community qigong classes were presented. Methods: Qualitative data were collected from an exit survey of 14 study participants with MS who enrolled in a pragmatic trial of community qigong classes for 10 weeks. Participants were new to community-based classes offered but some had experience with qigong/tai chi/other martial arts or yoga. Data were analyzed using reflexive thematic analysis. Results and Discussion: Seven common themes were identified from this analysis: (1) physical function, (2) motivation/energy, (3) learning, (4) dedicating time for self, (5) meditation/centering/focus, (6) relaxation/stress relief, and (7) psychological/psychosocial. These themes reflected both positive and negative experiences with community qigong classes and home practice. Self-reported benefits centered around improved flexibility, endurance, energy, and focus; stress relief; and psychological/psychosocial benefits. Challenges included physical discomfort including short-term pain, balance difficulty, and heat intolerance. Conclusion: The qualitative findings provide evidence to support qigong as a self-care practice that may benefit people with MS. The challenges identified in the study will help to inform future clinical trials of qigong for MS. Trial Registration: ClinicalTrials.gov (CTR#: NCT04585659).